Bilinguality and bimodality: Comparing linguistic and visual acculturation in artists' letters and their works. (April 2014) - Gardner-Chloros, Penelope
In this paper the letters of bilingual artists are proposed as a new source of evidence for understanding the relationship of bilinguality with individual identity. This approach is first situated within a more qualitative tradition in sociolinguistics, which allows the speaker's individuality to be understood in more depth. Thanks to having two modes of expression, linguistic and artistic, bimodal bilinguals provide new insights into the impact of being immersed in a new culture and language. A sample of the correspondence of two 19 th century bicultural and bilingual artists, Lucien Pissarro and Vincent van Gogh, is analysed. Comparisons are made between their linguistic style, especially their code-switching, and their biculturality as manifested in the artistic field. Their works, like their use of language, show the intermingling of influences of their culture of origin and that of their adoption. It is suggested on the basis of this study that investigating bimodal bilingualism may provide a bridge to help us understand the connections between language, identities and the way different cultural experiences are brought together.